EVALUATION OF AVAILABLE CODES FOR CAPACITY ASSESSMENT OF CORRODED PIPELINES - Belachew , Chanyalew Taye; Che Ismail, Mokhtar; Karuppanan , Saravanan (2009)
Evaluation of the capacity of corroded pipeline is an issue for several researchers and pipeline operators. Though there are various methods used for the assessment of remaining strength of corroded pipes, some of these methods are too much simplified and rely only upon the defect length and depth, ignoring the defect width and orientation. Moreover, most of these well known methods are limited to internal pressure and non interacting defects. In this paper evaluation of the most widely applicable corrosion assessment methods of ASME B31G, Modified B31G, RSTRENG, DNV RP-F-101 and PCORRC is conducted. As expected, the evaluation result shows that these methods are too much conservative. This means when pipeline operators use these codes for their fitness for service assessment; they are subjected to either unnecessary maintenance or premature replacement of pipelines. Therefore, further research towards the development of less conservative capacity assessment method based on burst test and nonlinear finite element method (FEM) is recommended.